2014
DOI: 10.3390/ani4020313
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptance of Dry Dog Food Variations

Abstract: Simple SummaryThe objectives of this study were to compare the acceptance of different dry dog food products by consumers, determine consumer clusters for acceptance, and identify the characteristics of dog food that drive consumer acceptance. Pet owners evaluated dry dog food samples available in the US market. The results indicated that appearance of the sample, especially the color, influenced pet owner’s overall liking more than the aroma of the product.AbstractThe objectives of this study were to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…The results of this research showed that the acceptability of the appearance of dry dog food by consumers is affected by the number of kibbles, color(s), shape(s), and size(s) present in the product. These results complement the results by Di Donfrancesco et al [ 15 ] who found that the color of the kibbles and the size of them affect the liking of dry dog food by consumers. The participants overall showed preference for single-kibble samples of brown colors, medium kibble sizes, and traditional kibble shapes such as triangular prisms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this research showed that the acceptability of the appearance of dry dog food by consumers is affected by the number of kibbles, color(s), shape(s), and size(s) present in the product. These results complement the results by Di Donfrancesco et al [ 15 ] who found that the color of the kibbles and the size of them affect the liking of dry dog food by consumers. The participants overall showed preference for single-kibble samples of brown colors, medium kibble sizes, and traditional kibble shapes such as triangular prisms.…”
Section: Discussionsupporting
confidence: 90%
“…From a sensory perspective, the interaction dog owners have with dog food is usually through the senses of sight and smell. Di Donfrancesco et al [ 15 ] studied the overall acceptability, aroma acceptability and appearance acceptability of dry dog food products by consumers in the United States. The results showed that the appearance is more important than the aroma in driving the consumers’ liking of dry dog food products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palatability of pet food products plays an important role for success on the market, but consumer acceptance of aroma and appearance of kibble needs to be understood as well [ 2 ]. Descriptive sensory analysis has been used to study sensory characteristics of dry and canned pet food products [ 2 , 3 , 4 , 5 ]. Pet foods can be complex in their characteristics as a wide variety of ingredients are utilized for different types of pet foods, such as dry, canned, or semi-moist products.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when tested in-home, it is possible to use questionnaires in order to enrich the information gathered. For example, additional data such as human perceptions of the food [ 19 ] or the animals’ enthusiasm to eat it [ 11 , 20 ] can be collected. Thus, owners can provide not only information about home environment and dietary history of their animal but also their impressions on the different diets and report any behavior or physiological modifications.…”
Section: Panels and Methods Classically Used To Assess Food Prefermentioning
confidence: 99%